Pengaruh pemberian jus jamur tiram terhadap kadar kolesterol, trigliserida, dan malondialdehid penderita hiperkolesterolemia - Fera Nofiartika; Yunita Indah Prasetyaningrum (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
The effect of white oyster mushroom juice (Pleurotus ostreatus) to total cholesterol, triglyceride, and malondialdehyde (MDA) levels in patients with hypercholesterolemiaBackground: The high incidence of hypercholesterolemia due to the wrong diet is a health problem that needs to be addressed immediately. One food ingredient that is being cultivated and believed to have a hypocholesterolemic effect is a white oyster mushroom (Pleurotus ostreatus). These foods contain water-soluble fiber (β glucans) and lovastatin which are useful for improving lipid profiles. Objective: To determine the effect of white oyster mushroom juice (Pleurotus ostreatus) to total cholesterol, triglyceride, and malondialdehyde (MDA) levels in patients with hypercholesterolemia. Methods: This is a quasi-experimental study with a pretest and posttest design. This study was conducted by giving white oyster mushroom juice (Pleurotus ostreatus) for 14 days and then measured its effect on total cholesterol, triglyceride, and MDA levels. The location of the study in Pisangan Tridadi Sleman and the respondent was adults aged 18-55 years who had hypercholesterolemia. Data collection of lipid profiles was taken from venous plasma blood after 12 hours of fasting. While MDA levels were measured by using the thiobarbituric acid (TBA) method. The changes in cholesterol, triglycerides, and MDA levels after administration of white oyster mushroom juice analyzed using paired-t-test and Wilcoxon signed-rank test. Results: The oyster mushroom juice affected decreasing triglyceride levels (2.27 mg/dL; p=0.023). There was no difference in the mean total cholesterol and MDA levels between before and after the intervention. Conclusions: Consumption of white oyster mushroom juice for 14 days significantly reduce triglyceride levels in patients with hypercholesterolemia.